2011
DOI: 10.1590/s0100-06832011000500007
|View full text |Cite
|
Sign up to set email alerts
|

Land-use systems affect Archaeal community structure and functional diversity in western Amazon soils

Abstract: SUMMARYThe study of the ecology of soil microbial communities at relevant spatial scales is primordial in the wide Amazon region due to the current land use changes. In this study, the diversity of the Archaea domain (community structure) and ammonia-oxidizing Archaea (richness and community composition) were investigated using molecular biology- (H' = 1,9629; D = 0,1715), cultivo agrícola (H' = 1,4613; D = 0,3309) e floresta secundária (H' = 0,8633; D = 0,5405

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
2
31
0
6
Order By: Relevance
“…Microbial groups related to environmental characteristics has been recognized as the most important mechanism controlling soil microbial communities [39] with chemical soil factors identified as a master variable explaining significant portions of the variation in soil microbial diversity and community structure at local [40,41], regional [42][43][44] and global [45,46] scales.…”
Section: Local Regional and Global Factors Affect Soil Microbial Commentioning
confidence: 99%
“…Microbial groups related to environmental characteristics has been recognized as the most important mechanism controlling soil microbial communities [39] with chemical soil factors identified as a master variable explaining significant portions of the variation in soil microbial diversity and community structure at local [40,41], regional [42][43][44] and global [45,46] scales.…”
Section: Local Regional and Global Factors Affect Soil Microbial Commentioning
confidence: 99%
“…Several studies have highlighted soil management as an important factor influencing soil microbiota structure (Jesus et al, 2009;Taketani and Tsai, 2010;Navarrete et al, 2011). However, the mechanisms involved in changes in soil microbial communities are not yet fully understood (He et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Illumina high-throughput sequencing platform has been employed to study microbial community composition and is reported to be accurate and rapid in the identification than traditional methods such as culture and serial dilution methods, Biolog system and biomarkers which often isolate only a few soil microbes (Klingler et al, 1992). Soil archaea are difficult to culture but molecular methods have been used to demonstrate the presence of archaeal 16S rRNA gene sequences in agricultural, grassland and forest soils (Navarrete et al, 2011).…”
Section: Introductionmentioning
confidence: 99%